2021
DOI: 10.1177/00405175211022628
|View full text |Cite
|
Sign up to set email alerts
|

A superhydrophobic and flame-retardant cotton fabric fabricated by an eco-friendly assembling method

Abstract: A novel eco-friendly and durable superhydrophobic and flame-retardant cotton fabric with fluorine-free, halogen-free was prepared via step-by-step dip-coating and spraying technology. At first, common cotton fabric was impregnated in the flame-retardant ethoxysilane-terminated phosphate polyurethane. Afterwards, methanol mixture containing silica nanoparticles, methyl triethoxysilane, and dihydroxy-terminated polydimethylsiloxane was sprayed on the surface of the cotton fabric. Finally, a flame-retardant cotto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…26 The peaks at 1080 cm −1 and 840 cm −1 were the characteristic peaks of P–O–C and P–OH stretching vibration in CPAS. 5,6,27 These results showed that CPAS was successfully synthesized.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…26 The peaks at 1080 cm −1 and 840 cm −1 were the characteristic peaks of P–O–C and P–OH stretching vibration in CPAS. 5,6,27 These results showed that CPAS was successfully synthesized.…”
Section: Resultsmentioning
confidence: 73%
“…26 The peaks at 1080 cm À1 and 840 cm À1 were the characteristic peaks of P-O-C and P-OH stretching vibration in CPAS. 5,6,27 These results showed that CPAS was successfully synthesized. As shown in Figure 4, TG measurements were carried out to analysis the thermal decomposition behavior of cotton waste and CPAS.…”
Section: Characterization Of Cpasmentioning
confidence: 73%
“…The resulting products could obtain the desired superhydrophobicity and be successfully employed in applications of oil-water separation, [114][115][116] self-cleaning, [117][118][119] sewage disposal, 120 anti-icing, 121 anti-corrosion, 122 drag-reduction of fluids, 123 medical gauze and bandaids, [124][125][126] and protective clothing. [127][128][129][130][131]…”
Section: Wearable Productsmentioning
confidence: 99%
“…However, the use of superhydrophobic materials in sensor fabrication often presents challenges such as limited flexibility, difficult integration, and high cost. In order to address these issues, researchers have started investigating the integration of superhydrophobic materials with flexible electronic technology to create superhydrophobic flexible sensors that possess de-icing capabilities [58], self-healing properties [59,60] or flame retardant properties [61]. Such sensors not only exhibit adaptability to extreme environmental conditions, but also possess excellent flexibility and integration, making them easily applicable to a wide range of devices.…”
Section: Introductionmentioning
confidence: 99%